Embodied Songs: Insights Into the Nature of Cross-Modal Meaning-Making Within Sign Language Informed, Embodied Interpretations of Vocal Music - Fisher, Vicky J. (Frontiers in Psychology, 2021)
Embodied song practices involve the transformation of songs from the acoustic modality into an embodied-visual form, to increase meaningful access for d/Deaf audiences. This goes beyond the translation of lyrics, by combining poetic sign language with other bodily movements to embody the para-linguistic expressive and musical features that enhance the message of a song. To date, the limited research into this phenomenon, has focussed on linguistic features and interactions with rhythm. The relationship between bodily actions and music has not been probed beyond an assumed implication of conformance. However, as the primary objective is to communicate equivalent meanings, the ways that the acoustic and embodied-visual signals relate to each other should reveal something about underlying conceptual agreement. This paper draws together a range of pertinent theories from within a grounded cognition framework including semiotics, analogy mapping and cross-modal correspondences. These theories are applied to embodiment strategies used by prominent d/Deaf and hearing Dutch practitioners, to unpack the relationship between acoustic songs, their embodied representations, and their broader conceptual and affective meanings. This leads to the proposition that meaning primarily arises through shared patterns of internal relations across a range of amodal and cross-modal features with an emphasis on dynamic qualities. These analogous patterns can inform metaphorical interpretations and trigger shared emotional responses. This exploratory survey offers insights into the nature of cross-modal and embodied meaning-making, as a jumping-off point for further research.